Survey of Faba Bean («Vicia faba» L.) Virus Diseases in Ethiopia - Abashamo Lencho; Abashamo Lencho; Abdulrazak Yusuf; Adane Abraham; Derese Gorfu; Kemal Ali; Khaled M. Makkouk; Nigusie Tadesse (Phytopathologia Mediterranea, 2007)
Surveys conducted in 1996 and 1997 to assess the status of virus diseases affecting faba bean in the major growing areas of Ethiopia indicated that leaf yellowing, rolling, necrosis and stunting were the most common disease symptoms. The highest visually-observed disease incidence in a field was 85%, recorded in the Wello region (north-eastern Ethiopia). When 3049 symptomatic samples collected from 211 fields from all over Ethiopia were tested by the tissue blot immunoassay (TBIA) for 14 viruses, 1592 samples (52.2%) were found to be infected with at least one virus. Faba bean necrotic yellows virus (FBNYV, genus Nanovirus) was the most frequent (63.2%), followed by luteoviruses (28.5%) [such as Beet western yellows virus (BWYV, genus Polerovirus, family Luteoviridae) and Bean leaf roll virus (BLRV, family Luteoviridae)] and Chickpea chlorotic dwarf virus (CCDV, genus Mastrevirus, family Geminiviridae) (3.1%). Mosaic/mottling symptoms were observed in some fields but incidence was always very low (